2020
DOI: 10.1007/s13204-020-01593-7
|View full text |Cite
|
Sign up to set email alerts
|

Bio-synthesis of silver nanoparticles with the brackish water blue-green alga Oscillatoria princeps and antibacterial assessment

Abstract: This study describes the morphology of a filamentous non-heterocystous blue-green alga (cyanobacterium) Oscillatoria princeps isolated from the Bhabakundalswara sea mouth, its use in biogenic synthesis of silver nanoparticles (AgNPs), along with antimicrobial studies using multidrug resistant (MDR) methicillin-resistant strains of Staphylococcus aureus (MRSA), Streptococcus pyogenes and Escherichia coli, isolated from clinical samples. The synthesized O. princeps -AgNPs were characterized with UV-visible spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Algal synthesis of AgNPs is especially interesting because of the high capacity of the algae to take in metals and reduce metal ions [ 38 ]. In line with this, Bishoyi, et al [ 39 ] fabricated silver nanoparticles using the brackish water blue-green alga Oscillatoria princeps . Furthermore, plants were used to produce AgNPs.…”
Section: Resultsmentioning
confidence: 82%
“…Algal synthesis of AgNPs is especially interesting because of the high capacity of the algae to take in metals and reduce metal ions [ 38 ]. In line with this, Bishoyi, et al [ 39 ] fabricated silver nanoparticles using the brackish water blue-green alga Oscillatoria princeps . Furthermore, plants were used to produce AgNPs.…”
Section: Resultsmentioning
confidence: 82%
“… 61 Bishoyi et al synthesized AgNPs using Oscillatoria princeps and assessed its antibacterial activity against MRSA , S. pyogenes and E. coli . 62 The authors reported that MIC values of AgNPs against MRSA , S. pyogenes , and E. coli were 100, 80, and 60 μg/mL, respectively. Additionally, the MIC values of AgNPs synthesized by Leptolyngbya sp.…”
Section: Resultsmentioning
confidence: 99%
“…The color change was confirmed by UV-Visible spectra at 200-750 nm, which confirmed the formation of AgNPs. The synthesized AgNPs demonstrated potential antibacterial activity against S. pyogenes and E. coli with inhibition zone sizes of (14-16) mm using the agar well-diffusion method [90]. In a similar study by Hamouda et al another marine cyanobacterium, Oscillatoria limnetica, was utilized for the biomimicry, capping and stabilization of AgNPs.…”
Section: Marine Cyanobacteriamentioning
confidence: 97%